The case of a crafting care workshop in Shenzhen : considering the experiences of middle-aged women and social order from the perspective of Confucian feminism : a thesis presented in fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Albany, New Zealand - Huang, Yuxin (Massey University, 2026)
Gender equality is often evaluated through the liberal constructs of individual autonomy and labour participation. In contemporary China, many women’s wellbeing and agency are also shaped through everyday negotiations of relational obligations within families, communities, and state-regulated public life. This thesis explores the lived experiences of a group of middle-aged Chinese women participating in a community handcrafting workshop located within a Party Masses Service Centre in Shenzhen. I examine how participants navigate formal (state-affiliated) and informal (peer-formed) infrastructures of support to secure safety, belonging, and practical resources in this space and beyond. I am particularly interested in how these arrangements enable participants to engage in and reflect on culturally resonant forms of gendered agency. Theoretically, thesis is guided primarily by Li-Hsiang Lisa Rosenlee’s reconstructive Confucian feminism, focusing on four core virtues: Xiao 孝 (Filial Piety); Ren 仁 (Humaneness/Benevolence); Li 礼 (Propriety/Ritual); He 和 (Harmony), as practical ethical tools rather than fixed patriarchal imperatives for participating women. Rosenlee’s work informed both the ethical orientation of the study and my interpretation of the accounts of four workshop members. Methodologically, I employed a qualitative case-based approach, combining sustained participant observation in the workshop (11 months) and four in-depth semi-structured interviews in Mandarin with four of the workshop members. The participants included Gang (lead instructor, retired), Hua (logistics manager, retired), Qiao (co-instructor, full-time housewife), and Wan (regular member, full-time housewife). These women represented a cross-section of the workshop’s roles and domestic contexts, offering rich insights into how middle-aged Chinese women navigate gender dynamics and relational wellbeing. Findings suggest that the workshop functions as an enclave of care that supports the wellbeing of participating women through institutional legitimacy and safety, peer-based practices of teaching and mutual support, and the re-articulation of Confucian virtues toward reciprocal responsibility and negotiated harmony. I argue that the everyday relational competencies displayed by workshop members constitute ethical expertise and a form of practical agency under the conditions of the present social order in China. This thesis contributes to feminist and community psychologies by exploring how women’s experiences and agency move them beyond a binary of oppression versus resistance. In acting with agency, participants balance the preservation of traditional relational values and responsibilities that are highly gendered, whilst seeking increased equity and agency for women. From exploring these issues and tensions with participating women, I reframe their relational labour as ethical expertise, and as a universal human competency rather than women’s naturalised responsibility.
Keywords: Confucian feminism; relational wellbeing; gender inequality; relational agency; Chinese women’s workshops; social order; rearticulations; 520501 Community psychology; 440502 Feminist methodologies